Design of a Digital Electrocardiograph with Arduino in Telemetry for the Elderly (LACCEI, 2024)
The present work has the purpose of designing and implementing a digital and wireless electrocardiograph, made with Arduino nano, capable of measuring the electrical activity of the heart at a distance, transmitting it and processing it through the Android Studio software, with the purpose that a cardiologist can obtain a diagnosis of the cardiovascular picture of the geriatric patient, mainly, without the need to transfer him to a hospital. This project consists of an Arduino nano, which performs two main functions, the first function is to execute the electrocardiogram readings, it is to place the ECG electrodes in the precordial and send the AD8232 signals to the Arduino nano, likewise in this in the first phase, the first 150 pulses must be collected, and these must be stored in RAM memory. The second function is to connect the RAID to the SIM 800L, a connection loop is executed to send the collected data and store it in the database. Next, the application developed in Android Studio goes on to graph the stored data. For the visualization of results, the collection time and data delivery time are considered. Various tests were carried out that conclude that the electrocardiograph telemetry shows an efficiency of 95.71%, corroborating the effectiveness of taking the electrical signal from the heart to detect different cardiac conditions. Therefore, it was concluded that it is feasible to carry out the design and construction of the project.